2009
DOI: 10.1177/1533317509332625
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Managing Wandering and Preventing Elopement

Abstract: Safeguarding wanderers from elopement risk is rendered person-centered and humane when goals of care guide intervention choice. Despite limitations, a reasoned, systematized approach to wandering management provides a basis for tailoring a specialized program of care. The need for framework refinement and related research is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…Environmental modifications include alterations made to the physical environment that camouflage or distract a person from a specific feature that is potentially hazardous to pass through, such as an exit door or a door to a room containing hazards. Such strategies aim to reduce boundary transgressions; the part of wandering associated with entry into out of bounds and hazardous areas (Moore, Algase, Powell‐Cope, Applegarth, & Beattie, ) and includes exit attempts or exiting behaviour. Three studies evaluated the efficacy of environmental interventions designed to encourage safer walking by reducing entry into areas that could be hazardous to the individual or accidental exits from an adult day care centre (Feliciano et al, ; Moore, ; Padilla et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental modifications include alterations made to the physical environment that camouflage or distract a person from a specific feature that is potentially hazardous to pass through, such as an exit door or a door to a room containing hazards. Such strategies aim to reduce boundary transgressions; the part of wandering associated with entry into out of bounds and hazardous areas (Moore, Algase, Powell‐Cope, Applegarth, & Beattie, ) and includes exit attempts or exiting behaviour. Three studies evaluated the efficacy of environmental interventions designed to encourage safer walking by reducing entry into areas that could be hazardous to the individual or accidental exits from an adult day care centre (Feliciano et al, ; Moore, ; Padilla et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The previous research in this area consists of studies that focus specifically on PWD lost in the community [2,4-8] as well as studies that focus specifically on wandering in formal care settings but include some information on exits or elopements [9-11]. In the review of this research, four factors were found to be characteristic of incidents in which a person with dementia who was missing.…”
Section: Introductionmentioning
confidence: 99%
“…Policy-mediated interventions include organizationally prescribed procedures such as wandering-specific admission screening, care planning, incident report, and elopement response policies (Moore et al, 2009). The disadvantage of policy-mediated intervention is adherence, may be absent, partial, or inconsistent (Moore et al, 2009).…”
Section: Policy-mediated Interventionmentioning
confidence: 99%
“…The disadvantage of policy-mediated intervention is adherence, may be absent, partial, or inconsistent (Moore et al, 2009).…”
Section: Policy-mediated Interventionmentioning
confidence: 99%